The Evolving Disclosure Landscape: How Changes in Technology, the Media, and Capital Markets Are Affecting Disclosure - MILLER, GREGORY S.; SKINNER, DOUGLAS J. (Journal of Accounting Research, 2015)
ABSTRACT Recent changes in technology and the media are causing significant changes in how capital markets assimilate and respond to information. We identify important themes in the disclosure literature and use this as a framework to discuss the conference papers that appear in this volume. These papers examine how managers’ disclosure practices are being affected by changes in technology, the media, and capital markets. While this work makes important progress, we discuss how continuing technological change and the emergence of new forms of media offer further opportunities for research on the role of disclosure in capital markets.